Enzymatic Biocatalyst using enzymes from Pineapple (Ananas comosus) Peel Immobilized in Hydrogel Beads - Fonseca, Aluísio Marques da; Colares, Regilany Paulo; Oliveira, Mauro Macedo de; Souza, Maria Cristiane Martins de; Monteiro, Rodolpho Ramiton de Castro; Araújo, Rinaldo dos Santos; Amorim, Aiala Vieira; Santos, José Cleiton Sousa dos; Alcócer, Juan Carlos Alvarado; Pinto, Olienaide Ribeiro de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The enzymatic extract from pineapple peels, considering the time factor, low cost and ease of preparation of the reaction system, makes the use of this plant material scrap an economical alternative for some reactions of synthetic interest. Therefore, this work aimed to prepare pineapple peel enzymatic extract containing bromelain, with and without mechanical grinding for a period of up to 9-days of extraction, and then immobilizing those extracts on hydrogel beads for their application as a biocatalyst to produce energy interest esters. The best protein content obtained was 1.95 mg mL-1 for 6-days with mechanical grinding, as for the hydrolysis of p-NPP (p-nitrophenyl palmitate), 0.0125 U.mL-1 for 1-day extraction with trituration. The best index esterification activity achieved for the lauric acid as a substrate was 1.8 U mL-1 at 1-day extraction without grinding. For the hydrogel beads immobilization, a maximum protein yield of 28.8% was obtained with the 1-day extract and mechanical grinding, and in terms of p-NPP activity, a yield of 40.6% for the immobilized with 9-day extract without mechanical grinding. The immobilized and dehydrated beads with 1-day extract without grinding took the best esterification activity, 7.2 U g-1 of biocatalyst. The best conversion performance in the biocatalysis of fatty esters was by esterification of the dodecanoate n-propyl, with 95.1% for a period of 48 hours of reaction. For the transesterification reaction, the methyl oleate yield reached 47.3% after 120 hours of reaction.